Profil Pemahaman Holistik Mahasiswa Pengajaran Mikro Kelas B tentang Pembelajaran Matematika Berbasis HOTS - Sulistyani, Niluh; Alfreda, Lucia Endy Gracia; Silvia, Silvia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2021)
Higher-order thinking skills (HOTS) are essential skills required in 21st-century learning. This study aims to describe students' understanding of HOTS-based mathematics learning holistically. The comprehension in question includes insight into HOTS-based mathematics learning, both general comprehension and HOTS-based mathematics instructional design, and an understanding of HOTS-based problems (insight and ability to solve problems). This research was a qualitative study with the subject of 16 students of class B Micro Teaching lectures. Data were gathered from context questionnaires and HOTS profile questionnaires, observations of learning practices, tests, and interviews. Data analysis used was a qualitative technique consisting of data reduction, data presentation, and drawing conclusions and verification. The results showed that the students had a good understanding of HOTS-based mathematics learning. HOTS is understood as a skill that requires critical and creative thinking in solving problems at the level of analysis, evaluation, and creation. The majority of HOTS-based learning activities were shown by giving HOTS questions. Students have a good understanding of HOTS questions but this is not the case in creating and solving problems. Students' ability in solving HOTS level questions still needs to be improved.